Adverse Reactions Produced by the Oral Polio Vaccine - Arias Segovia, Mesías (1971)
This work was done during immunization campaigns against polio by the Sabin oral vaccine, vaccinated children from 2 months to 10 years old. The number of children used in this study was of 1,138, of which 159 or side reactions is made ​​in 13.97%. The reactional manifestations were diarrhea in 50.32%, 21.38% high fever, malaise at 7.55%, 6.28% vomiting, nausea and abdominal pain in 3.77%, other manifestations were lesser percentage. The group of children who did more complications were between 10 months and 10 years of age.